2020
DOI: 10.1080/14719037.2020.1764081
|View full text |Cite
|
Sign up to set email alerts
|

Intra-organizational trust in public organizations – the study of interpersonal trust in both vertical and horizontal relationships from a bidirectional perspective

Abstract: The purpose of this paper is to enhance our understanding of intra-organizational trust in public organizations by studying interpersonal trust in both vertical and horizontal relationships from a bidirectional perspective. Previous research has focused on trust at a single level of analysis, ignoring influences from other organizational levels, which has led to gaps in our understanding of trust. In addition, few studies take a bidirectional perspective where a trustor is simultaneously a trustee and vice ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
(97 reference statements)
0
30
0
2
Order By: Relevance
“…Trust is considered to be a ‘social bond’ necessary to maintain different organizational structures [ 52 ]. The literature stresses that organizational trust plays a very important role in the functioning of any organization [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Trust is considered to be a ‘social bond’ necessary to maintain different organizational structures [ 52 ]. The literature stresses that organizational trust plays a very important role in the functioning of any organization [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…When management trusts team members' information sharing ability, misunderstanding could be avoided. Besides, Hasche et al (2020) also confirmed that vertical trust (i.e. trust between team members and management) fosters the development of horizontal trust (i.e.…”
Section: Discussionmentioning
confidence: 53%
“…These activities could also be classified as one of the knowledge management strategies -personalization, which adopts a "people-to-people" approach to connect people, to build a network, to facilitate interaction among members and to (finally) promote the knowledge sharing (Lo and Ng, 2015). Lastly, Hasche et al (2020) discussed the importance of intraorganizational trust in public organizations. Several key recommendations are considered as suitable measures for academic management.…”
Section: Discussionmentioning
confidence: 99%
“…Employees perceive trust in organizations as a global evaluation process, with positive expectations of oneself in risky situations (Jain, 2016;Lewicka and Pec, 2019). Vertical trust is generally more complex than the horizontal one because it involves power and control, which has a significant impact on subordinates (Hasche, Höglund and Mårtensson, 2020).…”
Section: Discussionmentioning
confidence: 99%